2000
DOI: 10.1182/blood.v96.3.885.015k22_885_893
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient gene transfer in naive human T cells with a murine leukemia virus-based vector

Abstract: Retroviral vectors based on the Moloney murine leukemia virus (MuLV) have become the primary tool for gene delivery into hematopoietic cells, but clinical trials have been hampered by low transduction efficiencies. Recently, we and others have shown that gene transfer of MuLV-based vectors into T cells can be significantly augmented using a fibronectin-facilitated protocol. Nevertheless, the relative abilities of naive (CD45RA+) and memory (CD45RO+) lymphocyte subsets to be transduced has not been assessed. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…The impact of IL‐7 on the phenotype of naïve T cells is controversial. Some studies have reported that IL‐7 does not alter the phenotype of naïve lymphocytes and has no effect on activation markers 39,46–48 . Others have observed that IL‐7 induces the up‐regulation of certain activation markers (CD25/CD95) but because these changes were not accompanied by conversion of the cells from CD45RA + to CD45RO + phenotype, these changes were classified as minimal 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…The impact of IL‐7 on the phenotype of naïve T cells is controversial. Some studies have reported that IL‐7 does not alter the phenotype of naïve lymphocytes and has no effect on activation markers 39,46–48 . Others have observed that IL‐7 induces the up‐regulation of certain activation markers (CD25/CD95) but because these changes were not accompanied by conversion of the cells from CD45RA + to CD45RO + phenotype, these changes were classified as minimal 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of retroviral transduction on CD45RA and CD45RO T cells has not been extensively studied. Dardalhon et al (2000) used a retroviral vector encoding eGFP and packaged with GALV to transduce mature PBMC and T cells from umbilical cord collections. Naive umbilical cord T cells were shown to switch from CD45RA to the CD45RO phenotype after 6 d of stimulation, and were transduced at lower efficiency than mature T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Optimization of culture conditions might contribute to increasing subsequent T‐cell function. We and others have observed that replacing OKT3/IL‐2 by CD3/CD28 at day 0 of cell culture might not only improve transduction efficiency [30] but also cell output [31], TCR diversity [29] and the frequency of anti‐EBV gene‐modified CD8 + T‐cells (Sauce et al ., submitted).…”
Section: Hurdlesmentioning
confidence: 99%
“…By increasing the polyclonality of GMC as well as reducing ex viv o culture time length, higher transduction efficiency might also contribute to enhancing overall immune function. Recently, technical improvements including use of Gibbon ape leukaemia virus enveloping pseudo‐typed retroviral vectors, CD3/CD28 costimulation, use of fibronectin‐coated plates as well as per‐transduction centrifugation have indeed resulted in improving transduction efficiency [30, 32–34].…”
Section: Hurdlesmentioning
confidence: 99%